As condições de expansão da Universidade Federal de Viçosa e de implementação do Programa de Apoio a Planos de Reestruturação e Expansão das Universidades Federais (REUNI) e suas repercussões no trabalho docente - Santana, Kátia de Cássia (2018)
The objective of the research was analyzed as implications of the expansion of the Federal University of Viçosa (UFV) and the implementation of the Federal University Restructuring and Expansion Plans Support Program (REUNI) in the teaching work. We sought to articulate some theoretical propositions about: the relations between changes in the world of work, State Reform and educational policies; the mediations of the relationship between work and education. We started from the assumption that the structural changes of capitalism have brought transformations to the world of work and to the teaching career that becomes marked by the logic of efficiency and the maximization of resources and the workforce. We also sought to investigate how the phenomena of the productive reconfiguration of the public university took place in the institution, as well as to indicate if there was a process of intensification of the teaching work at UFV after the implementation of REUNI. We defined UFV and professors of 5 departments that make up the undergraduate courses in the full-time Biological Sciences (Bachelor/Teaching Degree) and nocturnal Biological Sciences (Teaching Degree) as the empirical field of our object of analysis. Data collection included official, institutional and academic documents; the application of questionnaires to 60 professors about the teaching profile and vision about the expansion; conducting of 12 semistructured interviews on activities and daily life of the teaching work. We sought the relatively egalitarian participation of professors in different stages of the professional career (initial, intermediate and final) and they presented distinctions in relation to the activities in which they participated. Thus, respondents were professors who taught in graduate and undergraduate courses; professors who taught only at graduation; among professors who taught in postgraduate courses, those with different qualifications: fellow’s productivity - categories researcher 1 level A, B, C and D and 2, and professors who did not have them. We defined the following categories of analysis: working conditions; conflicts in work relationships; academic productivity and intensification of work. We sought to confront the analysis of professors' discourses, obtained through interviews, documentary data and questionnaires. It was possible to identify contradictions in the discourses and in the process of implementing the program. We point out that the process of intensification of teaching work is linked to the increase in the number of students and the demands of research productivity. We verified the managerialism engendered in the daily work with the predominance of indexes and goals to the detriment of the substantive professor’s work. The managerialist ideology tends to naturalize academic productivism and generate conflicts in work relationships, and the professors' complaints were reiterated in relation to each other regarding the distribution of management, teaching, research and extension tasks. We also considered that the reconfiguration of university practices in this context may threaten the quality of teaching and research in the institution. Thus, it was possible to indicate that REUNI: reproduces a managerial logic based on management and control mechanisms that, in the name of efficiency, generates competitiveness; implements courses with problems in the hiring of professors of the area, without finishing some buildings designed and with a deficit in the hiring of administrative technicians, as opposed to a considerable increase in the number of students. We have concluded that there is a tendency of naturalization of academic productivism and intensification of work, which leads to conflicts, unequal distribution of activities, and hierarchization among professors. And they admit that the qualitative dimension of teaching and research tends to be overwhelmed by the quantitative buyers of teacher performance evaluation.